39 Blood-derived endothelial progenitor cells from Von Willebrand's disease patients demonstrate that Von Willebrand factor regulates angiogenesis. Issue 20 (23rd September 2011) - Starke, R D; Paschalaki, K E; Ferraro, F; Dryden, N H; McKinnon, T A J; Sutton, R E; Payne, E M; Haskard, D O; Hughes, A D; Cutler, D F; Laffan, M A; Randi, A M
Abstract : Dysregulation of angiogenesis is implicated in many diseases. Von Willebrand factor (VWF), a large plasma glycoprotein essential for normal haemostasis is synthesised by endothelial cells (EC) and megakaryocytes. Raised VWF plasma levels are a risk factor for arterial thrombosis, while deficiency of VWF causes Von Willebrand disease (VWD), the most common congenital bleeding disorder in man. VWD can be associated with angiodysplasia, vascular malformations linked to defective angiogenesis. We hypothesised that VWF is involved in angiogenesis. To test this hypothesis, we isolated mononuclear cells from peripheral blood of controls and patients with VWD and cultured them to obtain confluent monolayers of blood outgrowth endothelial cells (BOEC). BOEC from VWD patients showed decreased VWF release, consistent with the patients' clinical data, increased capillary tube formation on Matrigel, migration and proliferation compared to controls. Thus BOEC from VWD patients exhibit enhanced angiogenic properties. Increased angiogenesis was also observed after inhibition of VWF expression in human umbilical vein EC (HUVEC) with specific siRNA. Mechanism studies on VWF siRNA-treated HUVEC implicated the endothelial VWF receptor, integrin α V β3 and the angiogenesis regulator angiopoietin-2. To validate our findings in an in vivo model we studied the VWF-deficient mouse. In vivo Matrigel angiogenesis and imaging of blood vessels in the ear showed increased angiogenesis and vascular network compared to littermate controls. Thus we have identified a novel mechanism for the regulation of angiogenesis and a new function for VWF, which may have clinical implications for VWD and for cardiovascular disease.